Analisis Pengetahuan Masyarakat terhadap Pemanfaatan Limbah Biji Salak (Salacca zalacca) Sebagai Identitas Budaya dan Sosial Masyarakat - Maspupah, Meti; Sa'adah, Sumiyati; Hidayah, Nurul (IMPACT: Journal of Community Service, 2025)
Salak seeds are one part of the salak fruit that is known as worthless waste by the community. Salak seed waste in some areas is used as raw material for making high-value coffee. This research aims to increase community participation in utilizing salak seed waste into a product that has high selling value and makes it a cultural identity of the Manonjaya region. This research data was obtained using a research questionnaire containing ten questions about snake fruit seed waste. The data obtained showed that most of the community did not know about the processing of salak seed waste into salak seed coffee. Data shows 96% of the community only consumes and utilizes the meat part of the salak fruit, 73% of the community has never consumed and utilized salak seeds. Based on these data, this research is expected to increase community participation in utilizing salak seed waste into a high-value product and make it a cultural and social identity of the Manonjaya region.